Kesan mangkin ke atas resin fenolik biopolimer dengan menggunakan kaedah pencecairan lignin soda - Sharifah Nabihah Syed Jaafar,; Sarani Zakaria,; Rozaidi Rasid,; Nurul Ain Zulkifli,; Ali Ahmadzadeh, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Liquefaction of soda lignin was carried using phenol with 1:3 ratio. The reaction time was 90 minutes at 130oC in the reflux system. The main product of liquefaction, phenolated lignin (PL), was analyzed by Fourier Transform Infrared Spectrometer (FTIR), rheometer and thermalgravimetri analyzer (TGA). The sample synthesized from hydrochloric acid as catalyst gave excellent characteristics. FTIR spectrum consists of essential functional groups such as aromatic ring, alcohol and carbonyl. All samples obeyed the Arhenius equation and showed pseudo-plastic properties. The percentage weight loss and degradation of PL samples were affected by the type of catalysts used. The synthesized PL was classified as biopolymer resin phenolic.